Spiritual Aspects of Care for Adolescents with Cancer. Issue 4 (July 2014) - Proserpio, Tullio; Ferrari, Andrea; Veneroni, Laura; Giacon, Barbara; Massimino, Maura; Clerici, Carlo Alfredo
Aims and Background: Adolescents with cancer have psychosocial issues that need to be adequately addressed. Spirituality is a fundamental aspect of their psychological well-being. Methods: A chaplain is a daily presence in the Youth Project ward for adolescents at the Pediatric Oncology Unit of the Istituto Nazionale Tumori, Milan. The chaplain conducts daily visits to the ward and the outpatient clinic/day hospital, holds daily meetings with the psychologists on staff, and attends biweekly meetings with doctors and/or nurses. The cases of patients referred for spiritual assistance between January and December 2012 were analyzed by patient age and reasons for consultation, and were compared with cases referred for psychological consultation. Results: A psychological consultation was offered to 84% of patients/families, and further support was needed for 23% of children and 45% of teenagers. Spiritual support was provided for 2 children and 20 adolescents (24% of the sample considered). Conclusions: Acknowledgment of their spiritual needs helps patients to battle with their disease. The reasons patients and parents ask for spiritual assistance only partially overlap with the motives behind requests to see a psychologist. The care of adolescents with cancer should include catering for their spiritual needs by assuring the constant presence of a chaplain on hospital wards.